1994
DOI: 10.1002/vnl.730160110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crystallinity on PVC physical properties

Abstract: Crystallinity in PVC contributes significantly to the strength and resiliency of the polymer. Two types of crystallites have been described: a primary crystallite in the virgin powder state pictured as a platelet or flat needle‐like lamellar crystallite, and a secondary, fringed micellar crystallite from melts or solutions. Both crystallites create loose, crosslinking networks. The secondary crystallite forms when plastisol melts are cooled or solutions are gelled. Crystallites exert a major effect on rheologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…With regard to the second temperature interval (160 -180°C), some authors have indicated that PVC is not a completely amorphous-glassy material. 1,7,23 This affirmation has been based on electronic microscopy and measurements. The proposal of a secondary crystallinity could justify the observation of a second stage in the gelation process due to the breaking of the primary crystalline structure.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…With regard to the second temperature interval (160 -180°C), some authors have indicated that PVC is not a completely amorphous-glassy material. 1,7,23 This affirmation has been based on electronic microscopy and measurements. The proposal of a secondary crystallinity could justify the observation of a second stage in the gelation process due to the breaking of the primary crystalline structure.…”
Section: Introductionmentioning
confidence: 73%
“…With regard to the second temperature interval (160–180°C), some authors have indicated that PVC is not a completely amorphous–glassy material 1, 7, 23. This affirmation has been based on electronic microscopy and measurements.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Detection of this temperature is contingent on the polymer achieving sufficient crystalline content. For example, poly(vinyl chloride), usually treated as an amorphous polymer, shows T m = 444 to 452 K when the crystalline content of the syndiotactic isomer is about 2 wt% [Marshall, 1994].…”
Section: Viscosity and Viscoelasticitymentioning
confidence: 99%